Can Adolescents Learn Self-control? Delay of Gratification in the Development of Control over Risk Taking - Romer, Daniel (2010)
Recent findings from developmental neuroscience suggest that the adolescent brain is too immature to exert control over impulsive drives, such as sensation seeking, that increase during adolescence. Using a discounting of delayed reward paradigm, this research examines the ability to delay gratification as a potential source of control over risk-taking tendencies that increase during adolescence. In addition, it explores the role of experience resulting from risk taking as well as future time perspective as contributors to the development of this ability. In a nationally representative sample (n=900) of young people aged 14–22, a structural equation analysis shows that risk taking as assessed by use of three popular drugs (tobacco, marijuana, and alcohol) is inversely related to the ability to delay gratification. The relation is robust across gender, age, and different levels of sensation seeking. In addition, high sensation seekers exhibit dramatic age-related increase in delay of gratification, lending support to the hypothesis that engaging in risky behavior provides experience that leads to greater patience for long-term rewards. The findings support the conclusion that a complete understanding of the development of self-control must consider individual differences not easily explained by universal trends in brain maturation.